2016
DOI: 10.1007/s00340-016-6369-0
|View full text |Cite
|
Sign up to set email alerts
|

Competition of single and double rescattering in the strong-field photoemission from dielectric nanospheres

Abstract: the carrier-envelope phase-dependent emission of single and double recollision electrons and find that both exhibit a characteristic directional switching behavior. This article is part of the topical collection "Ultrafast Nanooptics" guest edited by Martin Aeschlimann and Walter Pfeiffer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…While similar propagation-induced directional control of the electron emission has already been observed with CEP-controlled few-cycle pulses [19,37], those studies have been carried out at a single (central) wavelength, such that a change of the CEP allowed only for control of the up versus down emission, while the directionality could only be steered by changing the particle size. In the present study, we focus on an all-optical control of the emission angle, where in addition to having two distinct fields controlled via the two-color phase, the intensity ratio provides an extra parameter to control the relative strength of propagation induced asymmetry in the electron emission in single-size nanoparticles (shown here for 300 nm).…”
Section: Resultsmentioning
confidence: 80%
“…While similar propagation-induced directional control of the electron emission has already been observed with CEP-controlled few-cycle pulses [19,37], those studies have been carried out at a single (central) wavelength, such that a change of the CEP allowed only for control of the up versus down emission, while the directionality could only be steered by changing the particle size. In the present study, we focus on an all-optical control of the emission angle, where in addition to having two distinct fields controlled via the two-color phase, the intensity ratio provides an extra parameter to control the relative strength of propagation induced asymmetry in the electron emission in single-size nanoparticles (shown here for 300 nm).…”
Section: Resultsmentioning
confidence: 80%
“…However, when ρ ≥ 1, the dipole distribution begins to break down and higher-order terms significantly contribute, resulting in a shift of the maximum near-field enhancement towards the propagation direction. Previous theoretical work has shown that charge creation and interaction is enhanced in this regime and contributes to the acceleration [24].…”
Section: Photoelectron Emission From Nanoscale Particlesmentioning
confidence: 87%
“…These propagation effects are also referred to as nano-focusing and result in stronger field localization towards the propagation axis and larger field enhancement [34]. explanation might be derived from previous theoretical work, where the contribution of these nonlinear acceleration processes was studied as a function of particle size [24] . It was found that the trapping field contribution (in units of U p ) remains roughly constant, while the Coulomb explosion contribution grows significantly for larger particles due to the stronger confinement of the initial electron bunch.…”
Section: Size Dependent Photoelectron Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Süßmann et al 14 have revealed that electrons are generated on the nanoparticle surface in the regions of maximum field enhancement and subsequently accelerated in the local near-fields. It has been shown experimentally and theoretically that released electrons gain most of their final energy from a combination of the dielectrically enhanced laser field and a local trapping potential induced by ionization 14,15,28 .…”
Section: Discussionmentioning
confidence: 99%